Relationship Of Experience Of Industrial Field Practices With Work Readiness Of Graduates Of Family Welfare Education Study Program - Nadiatul Fadhilah Hendra; Asmar Yulastri (Universitas Negeri Padang, 2021)
This research basically wants to find answers to problems regarding the relationship of information to the world of work, student competencies and job readiness. This study aims to determine whether there is a significant relationship between experience in industrial practice and job readiness for graduates of the Family Welfare Education Study Program.This type of research is quantitative research with a correlation approach. The population of this study were students who graduated from the Family Welfare Education Study Program in 2015 totaling 106 students consisting of 68 students who graduated from Catering and 38 students who graduated from Fashion Design. The sampling technique used the Proportional Random Sampling method with a total of 51 students consisting of 33 students who graduated from Catering and 18 students who graduated from Fashion Design. The data collection technique uses a questionnaire (questionnaire) that has been tested for validity and reliability. To find out the relationship between Industrial Practice Experience and Work Readiness of Graduates of the Family Welfare Education Study Program using the Product Moment Correlation technique.The results of the study conclude that there is a positive and significant relationship between Industrial Field Practice Experience and Work Readiness of Graduates of the Family Welfare Education Study Program with a positive correlation coefficient of 0.457 and significant 0.001 < 0.05, then Ha is accepted.